Effectiveness of Meniran Leaf Extract (Phyllanthus niruri L.) as Immunostimulant in Vannamei Shrimp (Litopenaeus vannamei) Against Vibriosis Disease - Baiq Ainaya Amrini Wachid; Dewi Nur'aeni Setyowati; Fariq Azhar (Journal of Aquaculture and Fish Health, 2022)
Vibrio harveyi infection was an obstacle in shrimp culture. Meanwhile, the use of antibiotics in disease control was no longer effective, so the use of immunostimulants such as meniran leaves was the safest alternative. The purpose of this study was to determine the effect of adding different doses of meniran leaf extract (Phyllanthus niruri L.) to feed on the immune system of vannamei shrimp (Litopenaeus vannamei) which was challenged with Vibrio harveyi. This research was an experimental study using completely randomized design (CRD) consist of 5 treatments and 3 replications, namely, P1 (positive control): commercial feed + V. harveyi infection; P2 (negative control): commercial feed + 0.9% NaCl; P3: commercial feed + 0.5% Meniran leaf extract + V. harveyi infection; P4: commercial feed + 1% Meniran leaf extract + V. harveyi infection; and P5: commercial feed + 2% Meniran leaf extract + V. harveyi infection. The parameters observed were survival and immune response. Immune response analysis was carried out by counting hemocytes, phagocytic activation and total bacteria present in the shrimp intestines at the end of the study. The results of this study indicate that the addition of meniran leaf extract affects the immune system and the viability of vannamei shrimp. In conclusion, the addition of meniran extract to vannamei shrimp feed with a dose of 1% can improve the immune system and viability of vannamei shrimp against vibriosis.